The Relationship between Sudden Sensorineural Hearing Loss and Serum Sex Hormone Levels in Perimenopausal Women - Shaoxiong Wang; Ke Wang; Jing Zhang; Donglan Sun (IMR Press, 2024)
Background: The purpose of the study was to explore the relationship between sudden sensorineural hearing loss (SSNHL) and serum sex hormone levels in perimenopausal women, as well as to further investigate the influence of these indicators for SSNHL in perimenopausal women. Methods: A total of 156 patients with SSNHL and 149 healthy individuals during perimenopause who received treatment or underwent physical examination in the Fourth Hospital of Shijiazhuang from August 2023 to December 2023 were selected to participate in this retrospective cohort study. The variances in fundamental patient data were analyzed using the Mann-Whitney U test and Chi-square test. We employed multivariate logistic regression to examine the association between serum levels of follicle stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), progesterone (P), testosterone (T), prolactin (PRL) levels and the occurrence of SSNHL in perimenopausal women. Spearman analysis was used to analyze the correlation between perimenopausal women serum sex hormone levels and SSNH. Results: Compared to the non SSNHL group, the SSNHL group women had lower serum levels of E2 and P ((35.08 ± 12.49) pmoL/L and (0.63 ± 0.24) nmoL/L) vs. ((43.46 ± 10.17) pmoL/L and (0.84 ± 0.13) nmoL/L) (p < 0.05). Multiple logistic regression analysis demonstrated that E2 and P were both at higher risk with the development of SSNHL. Spearman correlation analysis found that E2 and P are negatively correlated with pure tone hearing threshold in perimenopausal women. Conclusions: SSNHL in perimenopausal women may be related to their serum levels of sex hormones.